2015
DOI: 10.1002/chem.201501599
|View full text |Cite
|
Sign up to set email alerts
|

A New Synthetic Route to Microporous Silica with Well‐Defined Pores by Replication of a Metal–Organic Framework

Abstract: Microporous amorphous hydrophobic silica materials with well-defined pores were synthesized by replication of the metal-organic framework (MOF) [Cu3 (1,3,5-benzenetricarboxylate)2 ] (HKUST-1). The silica replicas were obtained by using tetramethoxysilane or tetraethoxysilane as silica precursors and have a micro-meso binary pore system. The BET surface area, the micropore volume, and the mesopore volume of the silica replica, obtained by means of hydrothermal treatment at 423 K with tetraethoxysilane, are 620 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…Among the different strategies suggested in literature, the use of metal organic-frameworks (MOFs) as precursors for the synthesis of nanomaterials such as metal (oxide) nanoparticles 23 26 , porous silica 27 , 28 , or nanoporous carbons 29 offers unrivaled design possibilities, as we also demonstrate in this work. Herein we report a multi-step approach for the preparation of highly loaded Co on silica FTS catalysts that circumvents the interdependence between metal loading, active site dispersion, and accessibility.…”
Section: Introductionmentioning
confidence: 65%
“…Among the different strategies suggested in literature, the use of metal organic-frameworks (MOFs) as precursors for the synthesis of nanomaterials such as metal (oxide) nanoparticles 23 26 , porous silica 27 , 28 , or nanoporous carbons 29 offers unrivaled design possibilities, as we also demonstrate in this work. Herein we report a multi-step approach for the preparation of highly loaded Co on silica FTS catalysts that circumvents the interdependence between metal loading, active site dispersion, and accessibility.…”
Section: Introductionmentioning
confidence: 65%
“…(a) Experimental data (symbols) from five independent measurements of methanol adsorption in CuBTC at 298 ± 5 K. Different symbols are used to distinguish between different experimental groups, while filled or hollow symbols show different publications from one group. The fitted continuous isotherms used in our analysis are shown as solid curves, and the two isotherms classified as type 2 outliers are labeled.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Interestingly, powder X-ray diffraction (XRD) data revealed that the titania phase adopted the brookite polymorph, which likely is attributable to a stabilizing influence of the MOF pores, as well as the presence of Cu 2+ ions during its formation . More recently, this synthetic technique was further adapted for the preparation of microporous silica via hydrothermal treatment of tetraethoxysilane after loading within the HKUST-1 framework …”
Section: Hybridization Of Mofs With Ceramicsmentioning
confidence: 99%
“…112 More recently, this synthetic technique was further adapted for the preparation of microporous silica via hydrothermal treatment of tetraethoxysilane after loading within the HKUST-1 framework. 113 3.2. Templating by External Surfaces of MOF Crystals.…”
Section: Hybridization Of Mofs With Ceramicsmentioning
confidence: 99%